DUKUNGAN SOSIAL BAGI ORANG DENGAN HIV AIDS (ODHIV) MELALUI APLIKASI GO ZERO BERBASIS SMARTPHONE (PROTOTIP) MENGGUNAKAN METODE TECHNOLOGY ACCEPTANCE MODEL (TAM) - Esterilita, Mari; Yusuf, Husmiati (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
The need for the Go Zero application began during the Covid-19 period where PLHIV were one of the vulnerable groups exposed to the Covid-19 virus. Social restrictions in health services also limit services for PLHIV in taking medication and counseling services. The development of applications in the world of health not only helps patients access health services but also makes it easier for health workers to monitor and provide services. Social workers have a role in advocating and increasing social support for vulnerable groups, including HIV/IADS groups. Social support with its development is not only given directly but can also be done based on technology. This study aims to describe the Utilization of the Technology Acceptance Model (TAM) method as social support for PLHIV. The Technology Acceptance Model (TAM) method consists of 4 Aspects, namely Perceived Usefulness, perceived ease of use, attitude toward use, and behavioral intention to use. This study uses a Quantitative approach through the TAM approach which is analyzed descriptively. The number of respondents in this study was 30 people selected using the purposive sampling technique. Data collection methods were through questionnaires and literature studies. The results showed that PLHIV strongly agreed and accepted the Go Zero application with aspects of perceived usefulness (PU) with a percentage of 82.5%. Aspects of Attitude Toward Using (AT) with a percentage of 82.8%. Aspects of ease of use (PE) with a percentage of 85.67%. Aspects of Behavioral Intention to Use (BI) with a percentage of 83.06%. Based on this, it can be concluded that the use of the Technology Acceptance Model (TAM) method is considered very good and can increase social support for PLHIV. The results of the analysis of respondent acceptance of the GO ZERO Application are high, so it can be developed in increasing social support for PLHIV.